The Five-Day Capitol - Theresa Young (Symphony in the Flint Hills, 2013)
The First Territorial Capitol, located at Fort Riley, has seen many changes throughout its 158 years on the prairie.
Keywords: First Territorial Capitol; prairie; grassland; Fort Riley; Kaw River; territory; Kansas; Bleeding Kansas; slavery; anti-slavery; polling; vote; capitol; pro-slavery; free-state; Union Pacific Railroad; Junction City; Pawnee